Dosimetry-guided peptide receptor radionuclide therapy in neuroendocrine tumors: interim safety analysis of the DUONEN trial - Kolodziej, Maciej; Opalinska, Marta; Mikolajczak, Renata; Hubalewska-Dydejczyk, Alicja; Dedecjus, Marek; Kowalska, Aldona; Saracyn, Marek; Garnuszek, Piotr; Cieszykowska, Izabela; Januszkiewicz-Caulier, Joanna; Dlugosinska, Joanna; Durma, Adam Daniel; et al. (Frontiers in Endocrinology, 2025)
BackgroundPRRT with [177Lu]Lu-DOTA-TATE improves survival in advanced GEP-NETs, but fixed-activity dosing may result in undertreatment or unnecessary toxicity. Individualized dosimetry and tandem-PRRT with 90Y/177Lu have been proposed, but prospective randomized evidence is lacking.MethodsDUONEN is an ongoing multicenter, randomized phase 3 trial (N = 92 planned; 56 analyzed) comparing standard fixed-activity [177Lu]Lu-DOTA-TATE (arm A) with three dosimetry-guided regimens: arm B (177Lu+90Y, variable 90Y); arm C (177Lu+90Y, variable 177Lu); arm D (variable 177Lu). Organ dosimetry was performed after each cycle, with per-cycle activity modifications to respect kidney (23 Gy) and marrow (2 Gy) thresholds. Safety was assessed by laboratory, renal, and hepatic parameters.ResultsActivity reductions predominated in arms B and C, while increases were common in arm D. Median cumulative kidney and marrow doses were highest in arm C (29.1 Gy and 0.79 Gy, respectively), driven by 90Y contribution. Hematologic declines were observed across all arms, most prominently in lymphocytes and platelets, and correlated with marrow dose but not with categorical dose modifications. Renal function remained stable, and no clinically relevant hepatotoxicity occurred.ConclusionsThis interim analysis demonstrates the feasibility and safety of dosimetry-guided PRRT strategies, including individualized 177Lu escalation and tandem 90Y/177Lu. DUONEN provides the first randomized prospective evidence for isotope- and patient-tailored PRRT dosing. Long-term follow-up will clarify their impact on efficacy.Clinical trial registrationhttps://www.clinicaltrialsregister.eu/ctr-search/search?query=eudract_number:2020-006068-99, identifier 2020-006068-99.